HERMENEUTIKA AL-QUR’AN PERSPEKTIF MULLĀ ṢADRĀ - Kerwanto Kerwanto (Sekolah Tinggi Agama Islam Sadra, 2021)
This article tries to explain Al-Quran Hermeneutics (takwil) in the perspective of Mullā Ṣadrā. The core issue discussed in this article is the presentation of three theories that form the basic foundation of Al-Qur'an hermeneutics (takwil) in the Mullā Ṣadrā’s perspective: first, the level of meaning of the Qur'an; second, his view of clear (muḥkām) and vague (mutashābihāt) verses; third, his belief in the harmony between reason and revelation. Another interesting discussion that readers will find when reading this article is an explanation of the unique characteristics of Mullā Ṣadrā's interpretation, as well as Mullā Ṣadra's criticism and moderate attitude towards the various classifications of exegetical methodologies used by the commentators. Meanwhile, in the process of applying the interpretation, he invites us to explore the esoteric meaning (bāṭin) as deeply as possible, without leaving the exoteric meaning (ẓāhir).